Risks in the Making Travels in Life Insurance and Genetics - Van Hoyweghen, Ine (Care & Welfare, 2006)
Since the 1990s, the impact of genetic testing for insurance has been the subject of international debates. However, these have been rather speculative and abstract. In an effort to find new openings, the author explores this concern from an empirical sociological angle - by studying the insurance world from the inside, through an ethnographic study of the life insurance industry, exploring insurance practices and how insurers make risks, and underscoring the diversity of insurance markets, underwriting practices and strategies.